Status of Wildlife in Wild Ass Sanctuary (Little Nann of Kutch, Gujarat State, India) - Singh, H. S.; Soni, V. C. (Indian Forester, 1999)
Little Rann of Kutch is unique ecosystem in the world, which supports rare, endangered and endemic flora and fauna of the country. High conservation value has been accorded to the LRK by selecting area for one of the proposed biosphere reserve of the country. Expansion of salt work, firing practice by Indian Army, non-settlement of the sanctuary, grazing, invasion of Prosopis, crop raid by the wildlife, change in land-use pattern in and around the sanctuary and poaching are important threat factors responsible for degradation of the habitat and decline of the population of some of the wildlife. To conserve flora and fauna of the area effectively, it has become necessary to settle all legal issues so that the sanctuary is managed as per the Wildlife (Protection) Act, 1972. Although population of the Wild Ass has increased and animal has dispersed in new area of original habitat. Movement orthe Wild Ass in new area due to loss of habitat caused man-animal conflict. In background of this fact, it is necessary to improve the habitat by removing factor of degradation of the habitat and bringing back the original vegetation by eradication of Prosopis from some of the areas.